Analisis kadar natrium benzoat pada tauco yang dipasarkan dipajak kota Kisaran dengan metode spektrofometri ultraviolet - Nur’aini Dalimunthe; Yulia Kusumanti; Farida Umamy (Journal of Pharmaceutical and Sciences, 2023)
Background; One of the preservatives that is permitted for use in food is sodium benzoate.Sodium benzoate is a salt or ester of benzoic acid (C6H5COOH) that is produced commercially through chemical synthesis. Sodium benzoate is also known as sodium benzoate or sodium benzoate. This preservative is a salt of sodium benzoic acid, a polyunsaturated fat that is approved for use by the United States Food and Drug Administration (FDA) and has been used by food and beverage manufacturers for more than 80 years to prevent microbial growth.Sodium benzoate has the molecular formula C7H5NaO2 and molecular weight Appears as odorless or almost odorless white crystalline granules or powder, soluble in 2.8 parts water and 90 parts ethanol (95%). Objective; This research aims to determine the extent of benzoate found in Tauco which is marketed in the Kisaran City Market. Method; The analysis was carried out using a qualitative method with the aim of determining the Tauco benzoate content using the FeCl3 test, esterification test and sublimation test, quantitative methods using UV-Vis spectrophotometry and to determine the sodium benzoate content according to established standards. Absorbance was measured by UV-Vis spectrophotometry at a maximum wavelength of 225 nm. Result;The results showed that the sodium benzoate content was Ten Tauco samples are A= 125.8555 mg/kg, B= 71.1929 mg/kg, C= 98.9557 mg/kg, D= 174.3942 mg/kg and E = 78.9945 mg/kg.. meet The standard requirement for the maximum use limit is 450 mg/kg. Conclusion; The conclusion of this research is that the sodium benzoate content meets the requirements and does not exceed the maximum threshold set by BPOM No. 36 of 2021, namely 450 mg/kg Tauco.